Policy recommendations for pursuing a sustainable agriculture in a small rural community in Romania - Luiza Toma (Humboldt University of Berlin, Department of Agricultural Economics, Central and Eastern European Sustainable Agriculture International Research Project (CEESA), 2003)
The paper gives a range of sustainable agricultural policy recommendations, based on the results of the previous CEESA research phases. We begin by a brief presentation of the Romanian case study dealing with the environmental awareness of farmers, measured by means of agri-environmental indicators and discrete choice modelling. Then, we present the policy instruments dealing with non-point source pollution from agriculture, focusing on those applied in the European Union, that are most likely to be used in accession countries. Here we briefly introduce the Romanian environmental institutional and legislative framework, emphasising the existent water policy instruments. We end up by proposing sustainable agricultural policies that, based on the insights of our case study, we consider to be most appropriate for the case of Romania.
Keywords: 330; Agrarpolitik; Umweltpolitik; Gewässerschutz; Ländliche Entwicklungsplanung; Nachhaltige Entwicklung; Rumänien